Structural health monitoring intelligent concrete for airport and preparation method of structural health monitoring intelligent concrete
By using polycarboxylic acid water reducer, silica fume and fly ash dispersed carboxylated multi-walled carbon nanotubes in concrete, the problem of monitoring traditional concrete in airport environments is solved, and efficient structural health monitoring and safety improvement is achieved.
Patent Information
- Application Number
- CN202411361680.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional concrete is prone to cracks and deterioration in airport environments, and due to non-conductivity limitations, it is difficult to achieve structural health monitoring and real-time detection. Existing intelligent concrete has problems of inhomogeneity and high cost when dispersing carbon nanotubes.
Using polycarboxylic acid water reducer, silica fume and fly ash as dispersants, carboxylated multi-wall carbon nanotubes are dispersed with silica fume and fly ash through ultrasonic treatment to form a uniform conductive network to improve the conductivity of concrete and structural health monitoring capabilities.
It significantly improves the conductivity and piezoresistive response of concrete, realizes real-time monitoring of structural stress, strain and damage, enhances structural safety and operation and maintenance efficiency, and reduces material costs and construction complexity.
Smart Images

Figure CN119219376A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials and relates to intelligent concrete for structural health monitoring of airports and a preparation method thereof. Background Art
[0002] Traditional concrete is widely used in building and infrastructure components due to its excellent structural performance and economic benefits, especially in the construction of airports, bridges, roads and buildings. Cement concrete airport pavements are exposed to the complex and changeable airport environment. They are subject to complex environmental effects such as dry-wet cycles, freeze-thaw cycles and salt erosion, which are prone to cracks and other deterioration, affecting their safety and durability. In addition, with the development of the national economy, the air traffic volume on my country's airport runways has grown rapidly, and the proportion of heavy-loaded wide-body aircraft has continued to increase. The service performance of airport pavements has rapidly degraded under the repeated action of high-frequency impact loads, and diseases are frequent, affecting the normal operation of the airport. In severe cases, they even threaten the safety of aircraft takeoff and landing, bringing huge safety risks and economic losses to airport operations. Therefore, in order to ensure the safety and efficiency of aircraft operations, it is necessary to conduct regular and timely condition assessments of airport pavements.
[0003] However, traditional concrete has a significant limitation: it is essentially a non-conductive material, which limits its application in load monitoring, health assessment, and energy conversion. Therefore, the existing traditional concrete pavement condition monitoring methods mostly rely on visual means, but their accuracy and stability still need to be improved, and they cannot perceive damage that has not yet extended to the surface. Although the acoustic emission technology and ground penetrating radar technology developed later can perceive underground damage, they are expensive, data processing is complex, and the runway needs to be closed during detection, which interferes with airport operations. To this end, researchers have pre-embedded sensors in the pavement to achieve real-time monitoring of pavement performance, but because most sensors are distributed in a point-like manner, the perception range is limited. Although distributed optical fiber expands the monitoring range, its installation and maintenance costs are high and it is easily affected by temperature. In addition, the embedded sensors are heterogeneous with cement concrete, which brings potential risks to the durability of concrete pavements.
[0004] In recent years, in order to broaden the application scope of concrete, researchers and engineers have tried to enhance the functionality of concrete by doping various conductive materials. By adding conductive materials to concrete, such as adding steel fiber, carbon fiber or other conductive particles such as nano nickel, smart concrete with self-sensing ability is prepared. Smart concrete can sense changes in its internal structural state such as stress, strain and cracks. When external forces or environmental conditions change, the resistance or conductivity of these conductive materials changes accordingly, forming a detectable signal, thereby realizing the monitoring of structural health. In addition, in smart concrete, the conductive network formed by conductive materials can sense the stress or strain inside the concrete. Stress changes will cause changes in resistance in the conductive network. By monitoring these changes in resistance, the internal strain of the concrete can be inferred, and potential structural problems can be discovered. Especially in heavy load and high-frequency use environments such as airport runways, timely detection of stress changes is crucial to prevent structural failure. In addition, smart concrete can also be combined with wireless sensor networks (WSNs) to collect and transmit data in real time using embedded sensors or external devices. This integration makes real-time remote monitoring of large-scale infrastructure possible, avoiding the inconvenience and limitations of traditional manual detection.
[0005] Smart concrete is particularly suitable for health monitoring of airport runways. The runway pavement is subject to multiple factors such as high-frequency heavy loads of aircraft and environmental erosion for a long time, and is prone to problems such as cracks and settlement. Smart concrete can identify small changes in the structure at an early stage through its self-sensing function and provide data support for maintenance, avoiding more serious structural failures and reducing maintenance costs.
[0006] However, the traditional method is to add other conductive particles such as steel fiber, carbon fiber or nano nickel to concrete. Although these functional fillers can make concrete have a certain electrical conductivity, they often require a large dosage, which will affect the mix ratio of the original concrete, and may further affect the mechanical strength and workability of the concrete, or increase material costs.
[0007] Carbon nanotubes (CNTs) are an ideal material for improving the electrical conductivity of concrete due to their excellent electrical conductivity and mechanical properties. CNTs have a unique one-dimensional structure and a high aspect ratio, which allows them to significantly improve the electrical conductivity of concrete when added in trace amounts without excessively affecting its structural strength and working performance. However, it remains a technical challenge to evenly disperse CNTs in the cement matrix. Carbon nanotubes tend to form agglomerates in water, which leads to uneven dispersion in the concrete matrix, resulting in discontinuity in the conductive path, thereby reducing the overall electrical conductivity of the concrete.
[0008] In traditional methods, dispersants such as methyl cellulose, sodium dodecyl sulfate (SDS) and sodium dodecylbenzene sulfonate (NaDDBS) can promote the dispersion of CNTs to a certain extent, but they often have a negative impact on the mechanical properties and working performance of concrete due to unstable chemical properties or chemical reactions with cement substrates. For example, SDS and NaDDBS may affect the hydration reaction of cement, and methyl cellulose will introduce a large number of bubbles, resulting in a decrease in concrete strength or other adverse changes in physical properties.
[0009] Patent CN111517705A discloses a multi-walled carbon nanotube modified active powder concrete with a strength grade of C100 or above and a preparation method thereof. The method comprises the following steps: adding quartz sand and quartz powder weighed by weight into a mixer and stirring evenly to obtain a mixture; adding cement, fly ash, silica fume and copper-plated microfilament steel fiber weighed by weight into the mixture and mixing evenly to obtain a dry material; weighing water and a polycarboxylic acid high-performance water reducer by weight, adding carbon nanotubes to an appropriate amount of water, and ultrasonically dispersing for 6 minutes to obtain a multi-walled carbon nanotube mixed liquid; adding the polycarboxylic acid high-performance water reducer and the remaining water and the multi-walled carbon nanotube mixed liquid into the dry material and stirring evenly to obtain the multi-walled carbon nanotube modified active powder concrete. Although this patent adds fly ash and silica fume, it only ultrasonically disperses multi-walled carbon nanotubes and polycarboxylic acid water-reducing agent together, resulting in the inability of fly ash and silica fume to penetrate into the gaps created by the polycarboxylic acid water-reducing agent between the carbon nanotubes in a timely manner, affecting the steric hindrance effect of silica fume and the role of fly ash as a "ball bearing", and the effect of improving the dispersion stability is poor; in addition, this patent uses ordinary multi-walled carbon nanotubes, which have poor dispersion effect; in summary, the dispersion uniformity and dispersion stability of the preparation method of this patent need to be improved, resulting in uneven distribution of electrical conductivity in concrete, which cannot meet the electrical sensing performance requirements of concrete for structural health monitoring.
[0010] Patent CN107382205A discloses an ultra-high-strength high-performance fiber concrete with a strength grade of C160 and a preparation method thereof, the method comprising the following steps: dissolving 9.5 parts by mass of an activator and 2.6 parts by mass of a defoamer into water with a total water volume of 25%, recorded as aqueous solution 1, adding 14.0 parts of a water reducer, 40 parts of a hydroxyl-modified carbon nanotube dispersion and 37 parts of a graphene oxide dispersion into an aqueous solution with a total water volume of 50%, recorded as aqueous solution 2; weighing 750 parts of river sand and quartz sand configured in a mass ratio of 8:2, 100 parts of 0 parts of crushed stone and 1.6 parts of cellulose fiber are added to the mixer in sequence and stirred evenly for 2-3 minutes; then, 485 parts of cement, 70 parts of fly ash, 73 parts of rice husk ash, and 102 parts of silica ash are added in sequence, and the aqueous solution 1 is added to the mixer and stirred evenly for 2-3 minutes; then, the aqueous solution 2 is added to the mixer and stirred evenly for 3-4 minutes; finally, the fluidity of the mixture is observed, and the remaining 25% of the total water is added, and stirred evenly for 3-5 minutes, and the material is discharged to obtain the prepared concrete mixture; and it is molded and cured. Although the patent uses hydroxy carbon nanotubes to improve the dispersion effect of carbon nanotubes, it only uses mechanical stirring for dispersion, and its dispersion uniformity cannot meet the requirements of concrete for structural health monitoring for conductive uniformity.
[0011] Patent CN112679129A discloses a high-strength, corrosion-resistant carbon nanotube-modified concrete and a preparation method thereof. The raw materials of the concrete include a silicon dioxide-wrapped carbon nanotube composite material; the silicon dioxide-wrapped carbon nanotube composite material is prepared by the following method: adding carbon nanotube powder to deionized water, and then placing it in an ultrasonic oscillator, ultrasonically dispersing it, and preparing a carbon nanotube aqueous dispersion; mixing the carbon nanotube aqueous dispersion and a silica sol solution, and then ultrasonically treating them at the same frequency to keep the carbon nanotubes dispersed stably, and obtaining a suspension; performing a vacuum negative pressure drying treatment on the suspension to obtain a solid product; and performing a ball milling treatment on the dried solid product using a planetary ball mill to finally obtain a granular silicon dioxide-wrapped carbon nanotube composite material. Although this patent uses silicon dioxide to wrap carbon nanotube composite materials, which reduces the difficulty of dispersion, the ball milling process used in the preparation process will cause damage to the carbon nanotubes, resulting in a decrease in the aspect ratio of the carbon nanotubes, which significantly weakens the improvement of the electrical conductivity of concrete by the carbon nanotubes, making the electrical conductivity of concrete unable to meet the requirements of electrical sensing performance for concrete used in structural health monitoring; in addition, the vacuum negative pressure drying process and ball milling process used in the preparation process of this patent increase the complexity of construction, increase construction costs, and make it difficult to promote large-scale engineering applications. Summary of the invention
[0012] The purpose of the present invention is to provide an intelligent concrete for structural health monitoring for airports and a preparation method thereof in order to overcome at least one defect of the above-mentioned prior art. The present invention can effectively improve the electrical conductivity of concrete, thereby enabling it to have the function of monitoring structural health.
[0013] The purpose of the present invention can be achieved by the following technical solutions:
[0014] One of the technical solutions of the present invention is to provide a method for preparing smart concrete for structural health monitoring of airports, the method comprising the following steps:
[0015] S1, adding a polycarboxylate water reducer into water, mixing, and obtaining a water reducer solution;
[0016] S2, adding carboxylated multi-walled carbon nanotubes, silica fume and fly ash to the water reducing agent solution, mixing, and obtaining a preliminarily dispersed carbon nanotube suspension;
[0017] S3, subjecting the carbon nanotube suspension to ultrasonic treatment to obtain a fully dispersed carbon nanotube dispersion;
[0018] S4. Add the carbon nanotube dispersion into the dry material mixture and mix them to obtain the structural health monitoring smart concrete for airports.
[0019] Furthermore, in step S1, the solid content of the polycarboxylate water-reducing agent is 40-50wt%, the water reduction rate is 20-50%, and the added amount is flexibly adjusted according to the solid content of the polycarboxylate water-reducing agent and the mix ratio of concrete, and the added amount is 0.1-1wt% of the cement mass.
[0020] Furthermore, in step S2, the purity of the carboxylated multi-walled carbon nanotubes (CMWNTs) is greater than 90%, the outer diameter is 10-100 nm, the length is 10-100 μm, the carboxyl content is 1-2 wt%, and carboxylated multi-walled carbon nanotubes with a large aspect ratio are selected as much as possible. The added amount is adjusted according to the required conductivity and piezoresistive response, and the added amount is 0.05-0.25 wt% of the cement mass.
[0021] Furthermore, the mass ratio of the carboxylated multi-walled carbon nanotubes in step S2 to the polycarboxylate water-reducing agent in step S1 is 1:(2-4), and the mass ratio of the carboxylated multi-walled carbon nanotubes in step S2 to the water in step S1 is 1:(100-300), so as to prevent the fluidity from deteriorating during the dispersion process, causing uneven dispersion or damaging the dispersion equipment.
[0022] Furthermore, in step S2, the mass ratio of silica fume and fly ash to carboxylated multi-walled carbon nanotubes is (5-20):1.
[0023] Furthermore, in step S4, the dry material mixture includes cement and aggregate, the aggregate includes sand or stone with a particle size less than 8 mm, and the ratio of the dry material mixture is adjusted according to specific engineering requirements. The mass ratio of cement, aggregate and water added for mixing is (20-30):(40-60):(2-3).
[0024] Further, the mixing stirring speed in steps S1 and S2 is 1000-1500 rpm, and the time is 3-10 min;
[0025] The mixing time in step S4 is 1.5-6 min.
[0026] As a preferred technical solution, the dry material mixture in step S4 should be fully dry-mixed before adding the carbon nanotube suspension.
[0027] As a preferred technical solution, in step S4, the carbon nanotube suspension is added to the dry material mixture in two to five batches.
[0028] As a preferred technical solution, each batch needs to be stirred after being added in step S4.
[0029] Furthermore, the mixing in step S4 includes slow mixing and fast mixing to ensure that the carboxylated multi-walled carbon nanotubes are evenly distributed in the concrete matrix.
[0030] The slow stirring speed is 45-70rpm, and the time is 0.5-2min.
[0031] The stirring speed for rapid mixing is 150-300 rpm and the time is 1-4 min.
[0032] Furthermore, in step S3, the frequency of ultrasonic treatment is 15-25kHz, the power is adjusted according to the processing volume of a single ultrasound, the ratio of power to processing volume is 1kW:(0.5-0.8mL), and the time is 7-15min, so as to avoid the damage of the carboxylated multi-walled carbon nanotubes caused by too long ultrasonic time or the uneven dispersion caused by too short ultrasonic time. The ultrasonic treatment can fully break up the aggregates of the carboxylated multi-walled carbon nanotubes and improve their dispersion. The silica ash and fly ash are ultrasonically dispersed together with the carboxylated multi-walled carbon nanotubes, and the silica ash and fly ash can be timely penetrated into the gaps created by the polycarboxylate water reducer between the carboxylated multi-walled carbon nanotubes, which is beneficial to the steric hindrance effect of silica ash and the role of fly ash as a "ball bearing".
[0033] One of the technical solutions of the present invention is to provide an airport structural health monitoring smart concrete prepared by the method described above, the concrete comprising the following components in parts by weight:
[0034] 3-10 parts of polycarboxylic acid water-reducing agent, 1-5 parts of carboxylated multi-walled carbon nanotubes, 10-100 parts of silica fume, 10-100 parts of fly ash, 2000-3000 parts of cement, 4000-6000 parts of aggregate and 600-1000 parts of water.
[0035] One of the technical solutions of the present invention is to provide an application of the intelligent concrete for structural health monitoring for airports, wherein the concrete is applied to structural health monitoring of infrastructure, and the infrastructure includes an airport runway. The stress, strain and crack expansion inside the structure are sensed by detecting resistance changes to achieve self-monitoring of the structure.
[0036] The present invention provides a new method for preparing intelligent concrete. By using polycarboxylate water-reducing agent, silica fume (silicon dioxide) and fly ash as dispersants, while improving the workability of concrete and reducing the amount of cement, the efficient dispersing ability of the two can also significantly improve the dispersion quality of carbon nanotubes in concrete.
[0037] Compared with ordinary carbon nanotubes and hydroxylated carbon nanotubes, the surface of carboxylated carbon nanotubes carries more negative charges, and the hydrogen bonding effect with the polycarboxylic acid molecules in the polycarboxylic acid water-reducing agent is stronger, the adsorption effect is better, and electrostatic repulsion is generated, and a steric hindrance effect is formed to prevent the carbon nanotubes from reuniting; silica fume is inserted into the gaps between carbon nanotubes and can achieve self-assembly with carboxylated multi-walled carbon nanotubes, thereby utilizing its steric hindrance effect to improve the dispersion effect. The dispersed carbon nanotubes can be adsorbed on the surface of fly ash, and the spherical particles of fly ash are utilized to carry the carbon nanotubes and evenly disperse them in the cement concrete matrix. In addition, compared with other dispersants, polycarboxylic acid water-reducing agents have good chemical stability and compatibility with cement substrates, and silica fume with fine particle size can also play a role in filling micropores in concrete materials. The two not only avoid negative chemical reactions, but also further improve the mechanical properties and durability of concrete.
[0038] The present invention optimizes the usage ratio and dispersion treatment process of polycarboxylate water-reducing agent, silica fume and fly ash, and can achieve effective dispersion of carbon nanotubes without sacrificing working performance, thereby achieving high conductivity and excellent piezoresistive response of concrete. Furthermore, real-time monitoring of stress, strain and damage of concrete structure can be achieved by monitoring resistance changes, significantly improving structural safety and operation and maintenance efficiency.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) Improving the dispersibility of carbon nanotubes: By using polycarboxylate water-reducing agent, silica fume and fly ash as dispersants, and ultrasonically dispersing fly ash, silica fume and carboxylated multi-walled carbon nanotubes together, the present invention significantly improves the dispersibility of carboxylated multi-walled carbon nanotubes in the concrete matrix; the carboxylic acid groups on the main chain of the polycarboxylate water-reducing agent carry negative charges, which repel each other with the negative charges on the surface of the carboxylated carbon nanotubes, thereby increasing the electrostatic repulsion between the carbon nanotubes; and the long side chain portion of the polycarboxylate water-reducing agent forms a protective layer on the surface of the carbon nanotubes, thereby increasing the physical spacing between the carbon nanotubes and reducing the influence of the van der Waals force; and the fine particle size of silica fume helps it to insert into the gaps between the carbon nanotubes, and can achieve self-assembly with the carboxylated multi-walled carbon nanotubes, thereby utilizing its steric hindrance effect to improve the dispersion effect, and the spherical particles of fly ash play a lubricating role in the concrete, further reducing the friction and agglomeration between the carbon nanotubes; this not only prevents the reaggregation of the carboxylated multi-walled carbon nanotubes, but also enhances their stability in the matrix;
[0041] (2) Enhanced mechanical properties and durability of concrete: Compared with conventional dispersants, the use of polycarboxylate water-reducing agent, silica fume and fly ash in the present invention avoids adverse chemical reactions with the cement matrix, thereby not weakening the structural strength of the concrete; in fact, the addition of silica fume optimizes the microstructure of the concrete, enhances its compressive strength and durability, and thus provides higher structural safety;
[0042] (3) Improving electrical conductivity and piezoresistive response: The present invention significantly improves the electrical conductivity of concrete by effectively dispersing carboxylated multi-walled carbon nanotubes, so that concrete can monitor the stress, strain and damage of the structure in real time; the smart concrete of the present invention is suitable for key infrastructure such as airport runways. When the properties of the pavement itself deteriorate, its internal conductive path changes accordingly, and the resistance distribution also changes accordingly. Therefore, the health status of the concrete pavement can be continuously evaluated by monitoring the resistance distribution changes of the concrete pavement;
[0043] (4) Simple operation and construction, easy to apply and promote: The preparation method of the present invention is simple and easy to operate, the amount of carboxylated multi-walled carbon nanotubes added is small, and no major modification is required to the existing concrete mix design method. It is applicable to conventional concrete production facilities and processes, and does not require complicated operation steps, thereby ensuring its wide applicability and economic benefits in practical engineering applications;
[0044] (5) The amount of carboxylated multi-walled carbon nanotubes required by the present invention is extremely low, and will not significantly increase the production cost of concrete; it has a wide range of application and promotion potential economically, and is suitable for large-scale industrial production and application in various construction projects;
[0045] (6) The present invention adds carbon nanotubes to concrete and improves its uniformity of dispersion in the concrete matrix through certain methods, so that the concrete has self-sensing ability; smart concrete can sense the stress, strain and crack expansion inside the structure by detecting changes in resistance, thereby realizing self-monitoring of the structure; this function is particularly suitable for infrastructure such as airport runways that are subjected to heavy loads for a long time, and helps to detect problems in time at the stage of minor damage, thereby avoiding more serious structural failures;
[0046] (7) Traditional concrete structure monitoring usually relies on external sensors and regular manual inspections, which have the problems of low monitoring accuracy and limited coverage. The smart concrete prepared by the method of the present invention can achieve continuous and real-time structural health monitoring through the resistance change of the internal conductive network, and can monitor the health status of the entire structure without relying on external sensors. This real-time monitoring function significantly improves the safety of the structure and reduces the risk of sudden damage.
[0047] (8) The smart concrete of the present invention can sensitively respond to adverse conditions of the external environment (such as high-frequency impact, temperature change, etc.) by sensing stress changes in the environment; by continuously monitoring changes in resistance, timely feedback can be provided when changes in environmental conditions affect concrete, providing accurate data support for optimizing infrastructure maintenance and management strategies;
[0048] (9) The intelligent concrete technology of the present invention optimizes the mix ratio and reduces the installation of sensors, so that the concrete itself has monitoring functions, reduces the dependence on external monitoring equipment, reduces material costs and construction complexity, and is suitable for large-scale engineering applications. The promotion and application of intelligent concrete in key infrastructure will help improve the long-term reliability and economic benefits of infrastructure. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is a schematic diagram of a process for preparing smart concrete for structural health monitoring for airports according to an embodiment of the present invention;
[0050] Figure 2 A comparison chart of the resistance test results of concrete in the embodiment of the present invention and the comparative example;
[0051] Figure 3 A comparison chart of the temperature perception test results of concrete in the embodiment of the present invention and the comparative example;
[0052] Figure 4 This is a graph showing the stress perception test results of concrete in Comparative Example 1 of the present invention;
[0053] Figure 5 This is a graph showing the stress perception test results of concrete in Comparative Example 2 of the present invention;
[0054] Figure 6 This is a graph showing the stress perception test results of concrete in Comparative Example 3 of the present invention;
[0055] Figure 7 This is a graph showing the stress perception test results of concrete in Comparative Example 4 of the present invention;
[0056] Figure 8 This is a graph showing the stress perception test results of concrete in Comparative Example 5 of the present invention;
[0057] Fig. 9 Graph showing stress perception test results of concrete in an embodiment of the present invention. DETAILED DESCRIPTION
[0058] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0059] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0060] Example:
[0061] A type of intelligent concrete for structural health monitoring for airports, with specific mix proportions shown in Table 1.
[0062] Table 1 Specific mix ratio of smart concrete for airport structural health monitoring
[0063] Material water cement sand Silica Fume Fly ash Polycarboxylate water reducer Carboxylated multi-walled carbon nanotubes Mass(g) 770 2300 4300 23 23 6.9 2.3
[0064] The preparation method of the above-mentioned airport structural health monitoring intelligent concrete is as follows: Figure 1 As shown, the specific steps are as follows:
[0065] S1. Preparation of water reducing agent solution: Add 6.9 g of polycarboxylate water reducing agent with a solid content of 45 wt%, a water reduction rate of 30% to 500 g of water, and stir at a speed of 1200 rpm for 5 min using a magnetic stirrer to ensure that the water reducing agent is completely dissolved;
[0066] S2, preparation of carbon nanotube suspension: add 2.3g of carboxylated multi-walled carbon nanotube (CMWNTs) powder with a purity of 95%, an outer diameter of 30±10nm, a length of 20±10μm, a carboxyl content of 1.43wt%, and a mass of 2.3g, 23g of silica fume and 23g of fly ash to the water reducer solution, and continue to stir at a speed of 1200rpm for 5min using a magnetic stirrer to ensure that the carboxylated multi-walled carbon nanotubes are initially dispersed;
[0067] S3, ultrasonic treatment to prepare carbon nanotube dispersion: the carbon nanotube suspension was subjected to ultrasonic treatment twice, 250 mL each time, the frequency was 20 kHz, the power was 380 kW, and the time was 10 min, which can fully break up the aggregates of carboxylated multi-walled carbon nanotubes and improve their dispersion;
[0068] S4. Preparation of smart concrete for structural health monitoring for airports: Add the carbon nanotube dispersion into a pre-mixed dry material mixture three times. The dry material mixture is 2300g of cement and 4300g of standard sand with a particle size of 0.08-2mm; finally, use the remaining 270g of water to clean the cup wall and add it to the mixture; after each addition of the carbon nanotube dispersion or water, use a mechanical stirrer to slowly mix at a speed of 59rpm for 1min, and then quickly mix at a speed of 198rpm for 2min to ensure that the carboxylated multi-walled carbon nanotubes are evenly distributed in the concrete matrix.
[0069] Comparative Example 1:
[0070] A concrete and a preparation method thereof are basically the same as the embodiment, except that steps S2 and S3 are not taken, and in step S4, the carbon nanotube dispersion is replaced by the water reducing agent solution in step S1 to obtain concrete.
[0071] Comparative Example 2:
[0072] A concrete and a preparation method thereof are basically the same as those in the embodiment, except that all materials are directly dispersed by ordinary mechanical stirring to obtain the concrete.
[0073] Comparative Example 3:
[0074] A concrete and a preparation method thereof are substantially the same as those in the embodiment, except that silica fume and fly ash are not added in step S2, but are added as part of the dry material mixture in step S4.
[0075] Comparative Example 4:
[0076] A concrete and a preparation method thereof are basically the same as those in the embodiment, except that ordinary multi-walled carbon nanotubes are used instead of carboxylated multi-walled carbon nanotubes in step S2.
[0077] Comparative Example 5:
[0078] A concrete and a preparation method thereof are substantially the same as those in the embodiment, except that in step S2, hydroxylated multi-walled carbon nanotubes are used instead of carboxylated multi-walled carbon nanotubes.
[0079] The electrical resistance test of the concrete was carried out.
[0080] When preparing concrete specimens, electrode copper meshes were embedded at both ends of the specimens. The DC resistance of the specimens at 22°C was measured by the two-electrode method using a Keithley Instruments DMM6500 benchtop multimeter. The specimens were powered on for 2 hours before the test to reduce the influence of polarization during the measurement process. The experimental results are summarized in Figure 2 And Table 2.
[0081] Table 2 Comparison of resistance values of concrete of embodiment and comparative example
[0082]
[0083] like Figure 2 As shown in Table 2, the experimental results show that the conductivity of the airport structural health monitoring smart concrete prepared by the embodiment is significantly improved, not only the resistance value is low, but also the resistance value stability is high;
[0084] It can be seen that compared with the concrete mortar specimen without carboxylated multi-walled carbon nanotubes added in Comparative Example 1, the resistance of the concrete specimen prepared in the embodiment is significantly reduced;
[0085] Compared with the concrete carbon nanotube modified mortar specimens dispersed by ordinary mechanical stirring in Comparative Example 2 and the concrete specimens prepared in Comparative Example 3 with the addition of silica fume and fly ash after ultrasonic dispersion, the concrete specimens prepared in the embodiment have lower resistance and smaller dispersion.
[0086] Compared with the conventional multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes used in Comparative Examples 4 and 5, the concrete specimens prepared by using carboxylated multi-walled carbon nanotubes in the embodiment have smaller resistance dispersion.
[0087] When the pavement's own properties deteriorate, causing its internal conductive path to change, the resistance distribution also changes accordingly. The embodiment significantly reduces the resistance value of the concrete and improves the stability of the resistance value. Therefore, the concrete prepared by the present invention is easier to form a uniform internal conductive path, and the sensitivity and accuracy of sensing resistance changes are also higher. Therefore, continuous assessment of the health of the concrete structure can be achieved by monitoring the resistance distribution changes of the concrete pavement.
[0088] The above concrete was tested for temperature perception.
[0089] The resistance change of concrete at different temperatures was measured using a Teansi TA612C thermocouple thermometer to evaluate the concrete's perception of ambient temperature. The concrete was powered on for 2 hours before the test to reduce the impact of polarization during the measurement process. The experimental results are summarized in Figure 3 .
[0090] like Figure 3As shown, the experimental results show that the temperature perception performance of the airport structural health monitoring smart concrete prepared by the embodiment is significantly improved, not only the resistance value is low, but also the correlation and linearity of the resistance change with temperature are higher;
[0091] It can be seen that compared with the concrete mortar specimen without carboxylated multi-walled carbon nanotubes in Comparative Example 1 and the concrete carbon nanotube modified mortar specimen dispersed by ordinary mechanical stirring in Comparative Example 2, the concrete specimen prepared in the embodiment has lower resistance, and after linear fitting with temperature, the calculated R 2 It is significantly improved, indicating that the concrete specimens prepared in the embodiment have better linearity and higher correlation with temperature;
[0092] Compared with the addition of silica fume and fly ash after ultrasonic dispersion in Comparative Example 3, and the use of ordinary multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes in Comparative Examples 4 and 5, the concrete specimens prepared by using carboxylated multi-walled carbon nanotubes in the embodiment also have a better correlation with temperature.
[0093] The above concrete was subjected to stress perception test.
[0094] The resistance change of concrete under cyclic loading conditions was measured to evaluate the concrete's perception of its own stress. The loading cycle was 80s and the size was 6MPa (pressure). The resistance response was expressed as the resistance change rate ΔR / R (where R is the initial resistance and ΔR is the resistance change under a certain pressure). The concrete was powered on for 2h before the test to reduce the influence of polarization during the measurement process. The stress-resistance change rate experimental results are summarized in Figures 4 to 9 .
[0095] like Figures 4 to 9 As shown, the experimental results show that the stress perception performance of the intelligent concrete for structural health monitoring of airports prepared by the embodiment is significantly improved, the resistance change rate is significantly increased, and the perception sensitivity, stability and repeatability are higher;
[0096] It can be seen that compared with the concrete mortar specimen without carboxylated multi-walled carbon nanotubes added in Comparative Example 1, the concrete carbon nanotube modified mortar specimen dispersed by ordinary mechanical stirring in Comparative Example 2, and the concrete specimen with silica fume and fly ash added after ultrasonic dispersion in Comparative Example 3, the resistance change amplitude of the concrete specimen prepared in the embodiment is significantly increased, indicating that the concrete specimen prepared in the embodiment has higher perception sensitivity, and the resistance change curve is more continuous, and the resistance change repeatability is better during repeated loading, indicating that the concrete specimen prepared in the embodiment has higher perception stability;
[0097] Compared with the conventional multi-walled carbon nanotubes and hydroxylated multi-walled carbon nanotubes used in Comparative Examples 4 and 5, the resistance variation amplitude and repeatability of the concrete specimens prepared by the embodiment using carboxylated multi-walled carbon nanotubes are also improved, indicating that the perception sensitivity and stability of the concrete specimens prepared by the embodiment are also improved.
[0098] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing smart concrete for structural health monitoring of airports, characterized in that: The method comprises the following steps: S1, adding a polycarboxylate water reducer into water, mixing, and obtaining a water reducer solution; S2, adding carboxylated multi-walled carbon nanotubes, silica fume and fly ash to the water reducing agent solution, mixing, and obtaining a carbon nanotube suspension; S3, subjecting the carbon nanotube suspension to ultrasonic treatment to obtain a carbon nanotube dispersion; S4. Add the carbon nanotube dispersion into the dry material mixture and mix them to obtain the structural health monitoring smart concrete for airports.
2. The method for preparing smart concrete for structural health monitoring of airports according to claim 1, characterized in that: In step S1, the solid content of the polycarboxylate water-reducing agent is 40-50wt%, the water reduction rate is 20-50%, and the added amount is 0.1-1wt% of the cement mass.
3. The method for preparing smart concrete for airport structural health monitoring according to claim 1, characterized in that: In step S2, the carboxylated multi-walled carbon nanotubes have an outer diameter of 10-100 nm, a length of 10-100 μm, a carboxyl content of 1-2 wt %, and an addition amount of 0.05-0.25 wt % of the cement mass.
4. The method for preparing smart concrete for structural health monitoring for airports according to claim 1, characterized in that: The mass ratio of the carboxylated multi-walled carbon nanotubes in step S2 to the polycarboxylate water-reducing agent in step S1 is 1:(2-4), and the mass ratio of the carboxylated multi-walled carbon nanotubes in step S2 to the water in step S1 is 1:(100-300).
5. The method for preparing smart concrete for structural health monitoring for airports according to claim 1, characterized in that: In step S2, the mass ratio of silica fume and fly ash to carboxylated multi-walled carbon nanotubes is (5-20):
1.
6. The method for preparing smart concrete for structural health monitoring for airports according to claim 1, characterized in that: In step S4, the dry material mixture includes cement and aggregate, the aggregate includes sand or stone, and the mass ratio of cement, aggregate and water added for mixing is (20-30):(40-60):(2-3).
7. The method for preparing smart concrete for structural health monitoring for airports according to claim 1, characterized in that: The mixing speed in steps S1 and S2 is 1000-1500 rpm, and the time is 3-10 min; The mixing time in step S4 is 1.5-6 min.
8. The method for preparing smart concrete for structural health monitoring for airports according to claim 7, characterized in that: The mixing in step S4 includes slow mixing and fast mixing. The slow stirring speed is 45-70rpm, and the time is 0.5-2min. The stirring speed for rapid mixing is 150-300 rpm and the time is 1-4 min.
9. The method for preparing smart concrete for structural health monitoring for airports according to claim 1, characterized in that: The frequency of the ultrasonic treatment in step S3 is 15-25kHz, the ratio of power to treatment volume is 1kW:(0.5-0.8mL), and the time is 7-15min.
10. A smart concrete for airport structural health monitoring prepared by the method according to any one of claims 1 to 9, characterized in that: The concrete comprises the following components in parts by weight: 3-10 parts of polycarboxylic acid water-reducing agent, 1-5 parts of carboxylated multi-walled carbon nanotubes, 10-100 parts of silica fume, 10-100 parts of fly ash, 2000-3000 parts of cement, 4000-6000 parts of aggregate and 600-1000 parts of water.
Citation Information
Cited By
Intelligent detection test device for piezoelectric property of carbon nanotube-doped solid waste concrete
CN119846332A
Embedded salinity monitoring structure based on conductive concrete as well as preparation method and application of embedded salinity monitoring structure
CN122187442A
A buried salinity monitoring structure based on conductive concrete and a preparation method and application thereof
CN122187442B